Prognostic value of atherogenic index of plasma on the all-cause and causes-specific mortality among patients with metabolic dysfunction-associated steatotic liver disease - Guo Song; Heyu Chu; Yuting Liu; Xiaoli Liu; Rong Gu (Diabetology & Metabolic Syndrome)
Abstract Background The atherogenic index of plasma (AIP) has been proposed as a potential predictor of prognosis for atherosclerosis and cardiovascular disease (CVD). However, its prognostic value in patients with metabolic dysfunction-associated steatotic liver disease (MASLD) remains unclear. Methods This study included 4,062 participants with MASLD from the Third National Health and Nutrition Examination Survey (NHANES III). Kaplan-Meier curves, the Cox proportional hazards regression model, and restricted cubic splines (RCS) were used to assess the associations between the AIP and both all-cause and cause-specific mortality in patients with MASLD. Additionally, subgroup analyses and interaction test were conducted. Results During a median follow-up of 311 months, a total of 1821 (44.83%) all-cause deaths, 606 (14.92%) CVD deaths and 313 (7.71%) diabetes deaths occurred. After adjusting for potential confounding factors, the hazard ratios (HR) for the highest tertile (AIP ≥ 0.30) compared to the lowest tertile (AIP < 0.01) were 1.41 (95% confidence interval [CI]: 1.17–1.68; P < 0.001) for all-cause mortality, 1.49 (95% CI: 1.07–2.09; P = 0.019) for CVD mortality, and 2.27 (95% CI: 1.28–4.01; P = 0.005) for diabetes mortality. Furthermore, subgroup analyses revealed that the highest tertile of AIP was associated with an increased risk of CVD mortality in MASLD patients with diabetes (HR = 2.46; 95% CI: 1.46–4.13; P < 0.001) or obesity/overweight (HR = 2.36; 95% CI: 1.41–3.95; P = 0.001). Conclusions The elevated AIP is independently associated with all-cause mortality, as well as CVD and diabetes mortality in patients with MASLD. AIP can be used as a prognostic indicator for patients with MASLD.